2009
DOI: 10.1523/jneurosci.0617-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Frontoparietal Function during Recognition Memory in Schizophrenia: A Multimodal Neuroimaging Investigation

Abstract: Prefrontal-parietal networks are essential to many cognitive processes, including the ability to differentiate new from previously presented items. As patients with schizophrenia exhibit structural abnormalities in these areas along with well documented decrements in recognition memory, we hypothesized that these patients would demonstrate memory-related abnormalities in prefrontal and parietal physiology as measured by both functional magnetic resonance imaging and magnetoencephalography (MEG). Medicated outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
3
15
0
Order By: Relevance
“…A blocked design was selected in order to increase the SNR, optimizing our ability to detect very subtle BOLD changes associated with repetition priming in anterior and ventral temporal lobe regions that are known to be susceptible to signal loss (Chee et al, 2003; Dale et al, 2000). Although numerous studies have reported highly similar patterns of activations between blocked and event-related fMRI designs using lexical-semantic tasks (Chee et al, 2003; Pilgrim et al, 2002; Wagner et al, 2005; Weiss et al, 2009), blocked presentation of items may induce strategies or lead to greater levels of habituation in some regions relative to event-related designs. This may explain the bilateral precuneus and lateral occipitotemporal activations seen in our fMRI data that were not apparent with MEG.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A blocked design was selected in order to increase the SNR, optimizing our ability to detect very subtle BOLD changes associated with repetition priming in anterior and ventral temporal lobe regions that are known to be susceptible to signal loss (Chee et al, 2003; Dale et al, 2000). Although numerous studies have reported highly similar patterns of activations between blocked and event-related fMRI designs using lexical-semantic tasks (Chee et al, 2003; Pilgrim et al, 2002; Wagner et al, 2005; Weiss et al, 2009), blocked presentation of items may induce strategies or lead to greater levels of habituation in some regions relative to event-related designs. This may explain the bilateral precuneus and lateral occipitotemporal activations seen in our fMRI data that were not apparent with MEG.…”
Section: Discussionmentioning
confidence: 98%
“…Reliable decreases in blood-oxygen level dependent (BOLD) responses are consistently reported in left ventral occipitotemporal, posterior temporal, and left inferior frontal cortex—regions implicated in word form identification (Allison et al, 1999), lexical access, and semantic processing (Marinkovic et al, 2003; Matsumoto et al, 2005). Repetition of words also has been associated with increased activity in bilateral precuneus, frontoparietal, and hippocampal cortex—regions implicated in resting state and episodic retrieval processes (Weiss et al, 2009). What it not clear from fMRI is precisely when repetition effects occur during the course of word processing.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this frontoparietal network (FPN) is activated in tasks ranging from set-shifting (16) to feature selection (17) and object orientation (18) as well as recognition memory (19), working memory (20) and attention [for reviews see Ref. (2123)].…”
Section: Introductionmentioning
confidence: 99%
“…However, deficits in recognition memory that were related to nonsocial contexts were not directly compared in this study. Some studies have reported evidence of deficits in recognition memory that is related to nonsocial contexts as well (Kim, Kwon, Kang, Youn, & Kang, 2004; Weiss et al., 2009). Therefore, this viewpoint should be supported by the results of a task involving both social and nonsocial contexts, which should be able to determine whether the deficits were prominent during social contexts.…”
Section: Discussionmentioning
confidence: 99%